Editorial: Rising stars in parasite and host 2022 - De Niz, Mariana; Gold, Daniel A.; Kumar, Sudhir; Mast, Fred David; Richard, Dave; Simões, Maria L. (Frontiers in Cellular and Infection Microbiology, 2022)
Graphical Abstract